PENGARUH PENDAPATAN PERKAPITA, KURS DOLLAR DAN INFLASI AMERIKA SERIKAT TERHADAP EKSPOR MINYAK HEWANI DAN MINYAK NABATI INDONESIA PERIODE 1991-2017 - Pratini, Ni Wayan Ami Arya; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 2 (2021): VOL 10 NO 2, FEBRUARI 2021 [ 451 - 898], 2021)
The objectives to be achieved in this study are: 1) analyzing per capita income, the dollar exchange rate and the United States inflation simultaneously have a significant effect on exports of animal and vegetable oils in Indonesia in 1991-2017; 2) analyzing per capita income, the dollar exchange rate, and inflation in the United States partially have a significant effect on exports of animal and vegetable oils in Indonesia in 1991-2017; 3) analyze the influence of per capita income, the dollar exchange rate, and the inflation of the United States which is the most dominant influence on exports of animal oil and vegetable oil in Indonesia in 1991-2017. The analysis technique used in this study is Multiple Linear Regression Analysis. The results of this study are; 1) simultaneous income per capita, dollar exchange rate and United States inflation significantly influence the export of animal and vegetable oils in Indonesia in the 1991-2017 period; 2) per capita income has a positive and significant effect on Indonesia's animal and vegetable oil exports for the 1991-2017 period; 3) the dollar exchange rate has a negative but not significant effect on Indonesian exports in the 1993-2017 period; 4) inflation has a positive and significant effect on Indonesia's animal and vegetable oil exports for the 1991-2017 period; and 5) the variable that has the most dominant influence on exports is inflation with the greatest coefficient value of 1047,394. Keywords : Exports, income, exchange rates, inflation.